The Effect Of Follower In Increasing Leader’s Innovativeness And Firm Performance: Empirical Study PT. ”X” - Dedy Dewanto (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The objective of this research is to understand the process of developing leaders’ innovativeness in the context of a project-based organization with followers as the provider of ideas and knowledge, including how it turned into project performance. The research uses quantitative methods using deductive’s research process, where to answer the problem formulation, concepts or theories are used to formulate hypotheses. The hypothesis is then tested through field data collection. Conducted in a construction state own enterprise (SOE), selected due to tight competition and the consequential need for innovation within short timescales. The data collection involves 118 dyads of general managers (as leaders) and project managers (as followers). This research is based on a knowledge management model, which according to Dibella, Nevis and Gold (1996) comprises of knowledge acquisition, knowledge sharing and knowledge use, as well as on Nonaka and Takeuchi’s (1995) middle-up down model to foster innovation. The findings indicate the presence of vertical, middle-up flow of knowledge acquisition and sharing, that is, from followers to leaders in the development of leaders innovativeness. Yet, this research demonstrates the opposite effect in vertical, down flow of knowledge use in which leaders’ innovativeness may result in lower project performance. The hypothesis that Leader’s Innovativeness affects positively to Project’s Performance is not proven, but the effect is significantly negative. The reasons can be explained as follows: (1) Communication constraints, (2) External factor contraints during execution, (3) Setting target by Head Office is high, target reconciliation affected by external factor and cut off date, as well as company still adopt accounting system multi years bases, (4) Company do not perform Accumulated Knowledge Base, (5) The impact of innovation might be long term nature. Keywords: Followers Personal Mastery (FPM); Leader Member Exchange (LMX); leaders’ innovativeness; project performance.